QASHASH AL-QUR’AN AND ITS CONTRIBUTIONS IN PROFETIC CHARACTERS BUILDING OF YOUNG GENERATIONS, AN EXPERIMENTAL STUDY - Fadil, Muhammad Reza (At-Tibyan: Jurnal Ilmu Alqur`an dan Tafsir, 2020)
Theoretically, the stories in the Qur'an have the advantage to give more impression to human beings so that they can shape attitudes and behavior. Especially for young people, the method of storytelling is easier for them to accept the lessons. This is supported by preliminary findings that when the verses of the Qur'an are gathered which contain the word ?youth? in them, then all of the verses contain stories, so this research has a hypothesis that the stories of the Qur'an ( qashash al- Quran ) has an influence in the building of prophetic characters for the younger generation. Therefore, the purpose of this study is to find out whether there is an influence of the study of the Qur'anic qashash on the prophetic characters building in young generation. This research uses quantitative methods with the type of pre-experimental research using the one group pre-test post-test design. The selection of subjects in this study uses non-random sampling techniques with a purposive sampling method. The subjects of this study were twelve people with poor and good prophetic character categories. The study was conducted at the Faculty of Usuluddin Adab and Da'wah IAIN Langsa for six meetings. The instrument used is a Likert model of Prophetic Character Scale. While data analysis uses non-parametric statistical techniques using the Wilcoxon Signed Ranks Test with the help of SPSS version 17.00. The results showed that in general the study of qashash Al-Qur'an was relatively effective in shaping the prophetic character of students. While specifically this study obtained conclusions; there are differences in the average score of prophetic characters before and after the treatment is given in the form of a study of Qashash Al-Qur`an. Thus, it can be concluded that there is an influence of the study of Qashash Al-Qur`an on the prophetic characters building in students.